Doktrin Ketekunan Orang-Orang Kudus - Ceria Amelia; Chelsi Mellyanti; Difa Septiana; Sarmauli (Indo Publishing, 2026)
It is hoped that this research will provide a more comprehensive explanation regarding the definition and biblical basis for the doctrine of the perseverance of the saints, both in the Old and New Testaments, outlining and examining the theological rationale for the perseverance of the saints in the Christian faith tradition. The method used in this research is a literature study from collecting various secondary data sources. The research results show that the Bible, both in the Old and New Testaments, confirms that God calls His people to live holy lives and remain loyal to Him. Holiness is not a condition for salvation, but rather the fruit of the work of the Holy Spirit who works in believers after they receive the gift of salvation in Christ. Through the death and resurrection of Christ, the way of salvation is opened, and God Himself faithfully keeps His people from being separated from His love.